2007
DOI: 10.1016/j.wear.2006.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and tribological comparison of HVOF-sprayed and post-treated M–Mo–Cr–Si (M=Co, Ni) alloy coatings

Abstract: High velocity oxygen-fuel (HVOF)-sprayed wear resistant Co-28%Mo-17%Cr-3%Si and Ni-32%Mo-15%Cr-3%Si coatings, both as-sprayed and after heat treatments at 600• C for 1 h, have been studied. Particularly, their dry sliding wear behaviour has been compared by ball-on-disk tests against different counterbodies (100Cr6 steel and sintered alumina), and differences were discussed based on microstructural characteristics and micromechanical properties (Vickers microindentation and scratch test responses). As-sprayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 30 publications
4
18
0
Order By: Relevance
“…The overall damage experienced by these coatings is, however, negligible, which makes them comparable to the cermet layer and superior to electroplated chromium, tool steel and HVOF-sprayed Ni-Cr-Fe-Si-B-C. The large wear rate and high friction coefficient of this latter suggest severe adhesive wear, consistently with [33] and similarly to other Ni-and Co-based HVOF-sprayed coatings (tribaloys, inconel-625 and NiCrWMo alloys) tested under comparable conditions in previous studies [50][51][52]. These results therefore corroborate to the usefulness of Colferoloy coatings as alternatives to chromium plating and to Ni-based alloys.…”
Section: Rubber-wheel Abrasion Wear Testssupporting
confidence: 64%
“…The overall damage experienced by these coatings is, however, negligible, which makes them comparable to the cermet layer and superior to electroplated chromium, tool steel and HVOF-sprayed Ni-Cr-Fe-Si-B-C. The large wear rate and high friction coefficient of this latter suggest severe adhesive wear, consistently with [33] and similarly to other Ni-and Co-based HVOF-sprayed coatings (tribaloys, inconel-625 and NiCrWMo alloys) tested under comparable conditions in previous studies [50][51][52]. These results therefore corroborate to the usefulness of Colferoloy coatings as alternatives to chromium plating and to Ni-based alloys.…”
Section: Rubber-wheel Abrasion Wear Testssupporting
confidence: 64%
“…Thermal spraying is a common family of hardfacing techniques, which, compared to other processes (like welding techniques), are characterized by flexibility in coating material choice, low substrate thermal input and virtually no substrate dissolution [12]. Various thermal spray processes, such as detonation-gun, plasma and high velocity oxy-fuel (HVOF) spraying methods are mostly used to Vol.11,No6 Characterisation and corrosion-erosion behaviour 571 apply coating to impart a wear resistance against abrasion and erosion in corrosive environment at high temperature up to 900 °C [3].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the thermal fatigue behavior of the sintered coatings was greatly improved [17]. The heat treatment of amorphous coatings leads to the precipitation of sub-micrometric crystals [18], which definitely enhances the mechanical properties of coatings, such as the microhardness, fracture toughness and wear resistance [19][20][21][22]. Yoo et al [23] have found that the amorphous structured coatings exhibit a superior corrosion resistance to the crystallized coatings with high polarization resistance, and the The present study aimed at investigating the effect of post heat treatment on the microstructure and mechanical properties of arc sprayed Fe-based amorphous coatings.…”
Section: Introductionmentioning
confidence: 99%